Optimization of multi-tool machining process - Ahmed Alwaise, A. M.; Usubamatov, Ryspek, Prof. Dr.; M Zulkeffeli, Zain (International Network for Scientific Information Publication (INSI), 2012)
Link to publisher's homepage at http://www.insipub.com/